2013
DOI: 10.1016/j.bbmt.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Body Mass Index and Arm Anthropometry to Outcomes after Pediatric Allogeneic Hematopoietic Cell Transplantation for Hematologic Malignancies

Abstract: Although nutritional status may adversely affect various health outcomes, the relationship between anthropometry and outcomes after hematopoietic cell transplantation (HCT) has not been fully studied in children. We analyzed the impact of pre-HCT body mass index (BMI), arm muscle area, and arm fat area on outcomes in 733 patients age 2-18 years who underwent allogeneic HCT for a hematologic malignancy between 1985 and 2009. We evaluated these 3 variables according to patient group based on age- and sex-adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Supporting the inference that the effect of low albumin on outcome is dictated by its correlation with nutritional status are previous studies which show the importance of pre-HCT nutritional status to OS after HCT using more specific measurement tools such as BMI, bioimpedance and anthropometry [39–41]. As with ferritin, the prognostic value of serum albumin highlights a potential area of intervention (for example, aggressive nutritional supplementation pre-HCT) that could be targeted to improve outcome.…”
Section: Discussionmentioning
confidence: 91%
“…Supporting the inference that the effect of low albumin on outcome is dictated by its correlation with nutritional status are previous studies which show the importance of pre-HCT nutritional status to OS after HCT using more specific measurement tools such as BMI, bioimpedance and anthropometry [39–41]. As with ferritin, the prognostic value of serum albumin highlights a potential area of intervention (for example, aggressive nutritional supplementation pre-HCT) that could be targeted to improve outcome.…”
Section: Discussionmentioning
confidence: 91%
“…32,36,37 A recent study reported that pretransplant low arm muscle area was a stronger predictor than BMI of poor outcomes after HCT in children with hematologic malignancies. 38 The impact of pretransplant BMI, anthropometric measures and change of body weight should be assessed in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate nutritional status may increase the length of stay, as well as the risks of infections and mortality in hospitalized patients [9,13]. The nutritional deficit shown by the body mass index (BMI) and arm muscle area (AMA) has been associated with acute GVHD and relapse rate of the disease up to 100 days after transplant in pediatric patients [14]. Furthermore, the association of low oral food intake with development of severe GVHD after HSCT has also been observed [15].…”
Section: Introductionmentioning
confidence: 97%